Controlling anisotropy of porous B4C structures through magnetic field-assisted freeze-casting. Issue 5 (1st March 2022) - Bakkar, Said; Thapliyal, Saket; Ku, Nicholas; Berman, Diana; Aouadi, Samir M.; Brennan, Raymond E.; Young, Marcus L.
Abstract: Anisotropic porous boron carbide (B4 C) structures were successfully produced, for the first time, using the magnetic field-assisted freeze casting method. The effect of the magnetic field on the structure and mechanical strength of the formed porous B4 C was compared for two different magnetic field directions that were either aligned with ice growth (vertical), or perpendicular to the ice growth direction (horizontal). It was shown that applying even a weak horizontal magnetic field of 0.1–0.3 T noticeably affected the alignment of mineral bridges between lamellar walls. Both the porosity and the channel widths decreased with increasing horizontal magnetic field strength. In the case of a vertical magnetic field, a larger strength of 0.4 T was required for highly aligned lamellar walls and larger channel widths. Compression strength tests indicated that the application of magnetic fields led to more homogeneously aligned channels, which resulted in increased compression strength in the longitudinal (parallel to the ice growth) direction. Applying a vertical magnetic field of 0.4 T with a cooling rate of 2 °C/min during the freezing step of the magnetic field-assisted freeze-casting method was found to result in the best conditions for producing highly anisotropic structures with large channel widths and fewer mineral bridges, which led to an increase in the mechanical strength.